Out of band antenna characterization for EMC studies - Ke, Wai Loon. (2013)
This dissertation presents the EM modelling and study of the in band and out of band performance for the RF97 Vehicular Ultra High Frequency (UHF) Antenna which operates from 225MHz to 420MHz. It is important to understand the performance of not only the in-band performance of the antenna which consists of gain, polarization, beam width, pattern characteristics, but also crucially important for the out of band characterization. As in a complex platform, this kind of antennas will be of close proximity with each other and are located near to sensitive receiver system, thus Radio Frequency Interference (RFI) or Electromagnetic Interference (EMI) may occur.